2006
DOI: 10.1063/1.2348088
|View full text |Cite
|
Sign up to set email alerts
|

Vlasov simulation of amplitude-modulated Langmuir waves

Abstract: Mechanisms for the generation of Langmuir wave packets are studied by performing a one-dimensional electrostatic Vlasov simulation. The present simulation of a weak-electron-beam instability without ion dynamics suggests two new processes for the amplitude modulation of Langmuir waves. The beam instability excites Langmuir modes over a wide wave number range, but the saturation of the most unstable Langmuir mode “filters” the growth of sideband modes. Specific upper and lower sideband modes linearly grow to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…On the other hand, The GEOTAIL spacecraft observation in the magnetotail has shown that the amplitude of Langmuir wave packets is several hundred µV/m, which is too small for the Langmuir decay instability. The computer simulations have also demonstrated that amplitude-modulated Langmuir waves with a very small amplitude can be generated during a very-weak-electron-beam instability without ion dynamics (Akimoto et al, 1996;Usui et al, 2005;Umeda, 2006;Silin et al, 2007), which is consistent with the GEO-TAIL observation. These observations and simulations suggest that Langmuir wave packets with a small amplitude and a large amplitude are generated by different mechanisms with small amplitude packets generated by electron dynamics while large amplitude packets likely involve ion dynamics as well.…”
Section: Strongly Modulated Waveforms and Packets Of Langmuirsupporting
confidence: 78%
See 3 more Smart Citations
“…On the other hand, The GEOTAIL spacecraft observation in the magnetotail has shown that the amplitude of Langmuir wave packets is several hundred µV/m, which is too small for the Langmuir decay instability. The computer simulations have also demonstrated that amplitude-modulated Langmuir waves with a very small amplitude can be generated during a very-weak-electron-beam instability without ion dynamics (Akimoto et al, 1996;Usui et al, 2005;Umeda, 2006;Silin et al, 2007), which is consistent with the GEO-TAIL observation. These observations and simulations suggest that Langmuir wave packets with a small amplitude and a large amplitude are generated by different mechanisms with small amplitude packets generated by electron dynamics while large amplitude packets likely involve ion dynamics as well.…”
Section: Strongly Modulated Waveforms and Packets Of Langmuirsupporting
confidence: 78%
“…The amplitude modulation and packet formation of Langmuir waves were commonly observed in self-consistent kinetic simulations of electron beam instabilities (Muschietti et al, 1995(Muschietti et al, , 1996Akimoto et al, 1996;Matsukiyo et al, 2004;Usui et al, 2005;Umeda, 2006;Silin et al, 2007).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…2005; Baumgärtel, 2013) and electrostatic Vlasov simulations (Umeda, 2006;Silin et al, 2007;Umeda, 2007;Umeda and Ito, 2008;Daldorff et al, 2011;Sauer and Sydora, 2012). Studies which include ion dynamics (in some cases with a reduced proton-to-electron mass ratio) show clearly that the heavy particles indeed contribute to the evolution of the instability.…”
Section: K Baumgärtel: Ion Dynamics In Electron Beam-plasma Interactionmentioning
confidence: 98%